SISTEM PAKAR PENILAIAN TINGKAT KESEHATAN MENTAL MAHASISWA TINGKAT AKHIR MENGGUNAKAN METODE FAZZY INFERENCE SYSTEM (FIS) SUGENO - Triana Puspa Handayani; Khairul Saleh (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
The mental health of final year students is an important aspect in the world of higher education, especially in facing the demands of completing a thesis at the Faculty of Engineering, Asahan University. However, until now there is no system that can help assess students' mental health levels in a structured and automatic manner. Therefore, this research aims to design and build an expert system application using the Sugeno Fuzzy Inference System (FIS) method based on PHP and MySQL to assess the mental health level of final year students. The data used in this research was obtained through distributing questionnaires to final year students at the Faculty of Engineering, Asahan University. The variables used include stress intensity, sleep quality, academic load, and social interaction. The data obtained was 99 final year student respondents. The data processing was carried out using the FIS Sugeno method by forming fuzzy sets, membership functions, and 81 fuzzy rules to produce students' mental health levels. Based on the results of system testing, the FIS Sugeno method was successfully applied to automatically assess students' mental health levels. The system is capable of carrying out data input processes, fuzzification, fuzzy inference, and producing assessment output quickly and in a structured manner. The benefit of this research is that it helps provide an initial picture of the mental health conditions of final year students so that it can be taken into consideration in efforts to treat and assist students.